2006
DOI: 10.1007/s00213-006-0376-5
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide is involved in the memory facilitation induced by spermidine in rats

Abstract: These results suggest that memory enhancement by spermidine is prevented by the nonspecific nitric oxide synthase inhibitor L: -NAME.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 65 publications
1
11
0
Order By: Relevance
“…This facilitatory effect of systemically injected spermidine on memory is in agreement with the view that polyamines modulate memory by facilitating NMDA receptor activity (Berlese et al 2005;Guerra et al 2006;Kishi et al 1998a,b;Meyer et al 1998;Mikolajczak et al 2002;Nishiga and Kamei 2003;Rubin et al 2000Rubin et al , 2001Rubin et al , 2004Tadano et al 2004). In fact, it has been demonstrated that intrahippocampus and intra-basolateral amygdala administration of spermidine improves the consolidation of inhibitory avoidance and fear conditioning tasks, respectively (Berlese et al 2005;Guerra et al 2006;Rubin et al 2000Rubin et al , 2001Rubin et al , 2004.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This facilitatory effect of systemically injected spermidine on memory is in agreement with the view that polyamines modulate memory by facilitating NMDA receptor activity (Berlese et al 2005;Guerra et al 2006;Kishi et al 1998a,b;Meyer et al 1998;Mikolajczak et al 2002;Nishiga and Kamei 2003;Rubin et al 2000Rubin et al , 2001Rubin et al , 2004Tadano et al 2004). In fact, it has been demonstrated that intrahippocampus and intra-basolateral amygdala administration of spermidine improves the consolidation of inhibitory avoidance and fear conditioning tasks, respectively (Berlese et al 2005;Guerra et al 2006;Rubin et al 2000Rubin et al , 2001Rubin et al , 2004.…”
Section: Discussionsupporting
confidence: 83%
“…In fact, it has been demonstrated that intrahippocampus and intra-basolateral amygdala administration of spermidine improves the consolidation of inhibitory avoidance and fear conditioning tasks, respectively (Berlese et al 2005;Guerra et al 2006;Rubin et al 2000Rubin et al , 2001Rubin et al , 2004. In addition, the intracerebroventricular administration of spermidine antagonizes the deficits in working memory induced by 7-chlorokynurenic acid, a NMDA receptor antagonist, in the radial maze (Nishiga and Kamei 2003) and attenuates the memory impairment induced by olfactory bulbectomy in the passive avoidance task (Tadano et al 2004).…”
Section: Discussionmentioning
confidence: 97%
“…Several studies suggest that NO plays a role in synaptic plasticity and memory (Susswein et al 2004), and intrahippocampal administration of NO inhibitors has been shown to impair learning processes (Guerra et al 2006;Tan 2007). This effect could have interfered in the learning component (association between the drink spout and electrical shocks) of the Vogel test.…”
Section: Discussionmentioning
confidence: 97%
“…Current behavioral and neurochemical evidence suggests that the facilitatory effect of spermidine on memory depends on nitric oxide synthase (NOS) activity because the administration of N(G)-nitro L-arginine methyl ester (L-NAME), which is a nonspecific inhibitor of NOS, prevents the facilitatory effects of spermidine on the inhibitory avoidance task (Guerra et al 2006). In addition, Guerra et al (2011Guerra et al ( , 2012 showed that protein kinase A (PKA) and PKC inhibitors prevent the facilitatory effect of spermidine on the memory of an inhibitory avoidance task.…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%